Adoption of Yolk Antibodies in the Prevention and Diagnosis of Diseases in Aquaculture - Xinwei Wang; Rongwei Zheng (Journal of Animal and Plant Sciences, 2025)
This research aimed to evaluate the prevention, treatment, and diagnostic methodologies for aquaculture diseases based on egg yolk antibodies (Immunoglobulin Y, IgY) and assess their impact on the health of aquatic animals. Initially, IgY was prepared using sterilization, pH adjustment, centrifugation, dialysis, and other steps. The purity of IgY was examined using sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE), and its concentration was determined using the bicinchoninic acid (BCA) protein quantification assay kit. The potency of IgY against common aquatic pathogens was assessed using the enzyme-linked immunosorbent assay (ELISA). Subsequently, 60 health specimens (including crucian, eel, little snapper, smelt, turtle, and flounder) were randomly divided into the IgY group and Control group, with 30 in each. Meanwhile, another 60 infected specimens were randomly divided into IgY-1 group (IgY), Control-1 group (saline) and Control-0 group (no treatment), with 20 in each group. Serum IgY levels in healthy and infected aquatic animals were measured, and egg yolk antibody levels were determined using ELISA to assess the diagnostic efficacy of IgY. Changes in disease resistance, abnormal symptoms, and survival rates among the four groups were observed.The prepared IgY exhibited high purity (showing distinct blue bands between 80~70 kDa and 23~32 kDa) with a concentration of 1.78 mg/mL. IgY demonstrated good efficacy against Aeromonas hydrophila, Edwardsiella tarda, Vibrio anguillarum, and non-01 Vibrio cholerae. The serum IgY levels in infected aquatic animals were notably higher than those in healthy ones (P≤0.05). Evaluation of the diagnostic effectiveness revealed good sensitivity (76.67%), specificity (68.33%), and accuracy (72.50%) of IgY. Observations on preventive effects showed that at 1 month (M1), 3 months (M3), and 6 months (M6) after injection, the IgY group exhibited considerably higher body temperature, food intake, swimming behavior scores, and survival rates versus Control group. The proportion of abnormal symptoms was considerably lower in the IgY group versus Control group (P≤0.05). In the treatment observations at M1, M3, and M6, the IgY-1 group showed considerably higher food intake, swimming behavior scores, and survival rates than those in the Control-1 and Control-0 group, and a considerably lower proportion of abnormal symptoms (P≤0.05). At M3 and M6, the body temperature in the IgY-1 group was higher than that in Control-1 and Control-0 group (P≤0.05). IgY, as a preventive, therapeutic, and diagnostic approach, significantly enhanced the survival rate of aquatic animals in aquaculture, reduced abnormal symptoms, and improved overall health. It provides an effective strategy for disease prevention and diagnosis in aquaculture.
Keywords: IgY; aquaculture; prevention; treatment; diagnose